Tutoria instrucional centrada na leitura de livros em escolares com distúrbio de aprendizagem e dislexia do desenvolvimento - Machado, Andrea Carla (Universidade Federal de São Carlos, 2009)
The aim of this study was to evaluate the effects of instructional tutorship focused on book reading in students with developmental dyslexia and learning disability based on the proposals of Clay s Reading Recovery Program (1993). Among the specific objectives, the study aimed at characterizing the performance in percentage and identify the strategies related to reading and writing found in pre and post-testing of all groups involved in the research (with and without intervention) and compare, in pre and post-testing, the results of students with developmental dyslexia and learning disability. A group of twelve students participated in the study, and group I (DL) was subdivided into: GDL1 composed of three students with developmental dyslexia that participated in the intervention and GDL2 consisting of three students with developmental dyslexia that did not participate in the intervention. Group II (DA) was subdivided into GDA1 consisting of three students with learning disability that participated in the intervention and GDA2 consisting of three students with learning disability that did not participate in the intervention. The research presented the design: pretesting, tutorship, post-testing. The data were collected in sessions held in pre and post-testing with tasks of the Diagnostic Survey (Clay, 1993). The interventions, based on instructional tutorship, were performed in twelve individual sessions, once a week, lasting one hour each during the first semester of 2008. The results were analyzed in a descriptive way by the score in percentage of correct answers. Positive effects were verified on the teaching of strategies and the study also provides strong evidence that instructional tutorship focused on book reading gives students with developmental dyslexia and learning disabilities benefits with significant differences shown by the development of students who participated in interventions. However, the results of this study revealed that there was an improvement in the tasks that were observed and strategies that were trained in students with a learning disability when compared with students with developmental dyslexia.
Keywords: Distúrbios da aprendizagem nas crianças; Tutoria; Dislexia; Tutorship; Developmental dyslexia; Learning disability; Intervention; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL